Vermicomposting of water hyacinth [Eichhornia crassipies Mart. (Solms)] employing native and exotic earthworm species - H, Deka; S, Deka; CK, Baruah; P, Sarmah; J, Das (Journal of Research in Biology, 2012)
A laboratory experiment on vermicomposting of water hyacinth was carried out in two seasonal trials covering summer and winter period. The indigenous and exotic earthworm species Perionyx excavatus and Eudrilus eugeniae respectively were employed during the study and a comparative efficacy between the two vermi species was quantified. The experiment was conducted in earthen pots using the mixture of water hyacinth (WH) and cowdung (CD) in the ratio of 5:1. The results revealed that both the earthworm species can efficiently convert the substrate mixture (i.e. WH+CD) into value added material (i.e. vermicompost) although the Perionyx excavatus showed better efficiency as compared to the Eudrilus eugeniae. The results also revealed that vermicompost of Perionyx excavatus showed higher level of nutrient contents (N, P, K, Ca, Mg, Fe, Mn, Zn and Cu) as against Eudrilus eugeniae. There also found to be seasonal influence on the overall vermicomposting process and summer was found to be more productive as compared to the winter.